Bordetella pertussis outer membrane vesicles as virulence factor vehicles that influence bacterial interaction with macrophages - Blancá, Bruno Martin (2022)
Gram-negative pathogenic bacteria constitutively shed outer membrane vesicles(OMVs) which play a significant role in the host-pathogen interaction, eventually determiningthe outcome of the infection. We previously found that Bordetella pertussis, the etiologicalagent of whooping cough, survives the innate interaction with human macrophages remainingalive inside these immune cells. Adenylate cyclase (CyaA), one of the main toxins of thispathogen, was found involved in the modulation of the macrophage defense response,eventually promoting bacterial survival within the cells. We here investigated whether B.pertussis OMVs, loaded with most of the bacterial toxins and CyaA among them, modulatethe macrophage response to the bacterial infection. We observed that the pre-incubation ofmacrophages with OMVs led to a decreased macrophage defense response to the encounterwith the bacteria, in a CyaA dependent way. Our results suggest that CyaA delivered by B.pertussis OMVs dampens macrophages protective function by decreasing phagocytosis andthe bactericidal capability of these host cells. By increasing the chances of bacterial survivalto the innate encounter with the macrophages, B. pertussis OMVs might play a relevant rolein the course of infection, promoting bacterial persistence within the host and eventually,shaping the whole infection process.